대장직장암에서 Survivin과 HSP90 단백발현과 예후인자와의 관계 - 김택현(Taeg Hyun Kim); 이태진(Tae Jin Lee); 김범규(Beom Gyu Kim); 차성재(Sung Jae Cha); 박성준(Sung Jun Park); 임현묵(Hyun Muck Lim); 박성일(Sung Il Park) (Annals of surgical treatment and research, 2006)
Purpose: Survivin is an inhibitor of apoptosis protein and it is overexpressed in most human cancers. Recent data demonstrated that survivin-HSP90 complex regulate apoptosis. We assessed expression of survivin and HSP90 by using immunohistochemistry with colorectal cancer tissue and correlate it with clinicopathologic prognostic parameters. Methods: Using immunohistochemistry, survivin and HSP90 expression were evaluated on paraffin sections of fifty-six colorectal carcinomas. Various clinicopathologic parameters including histologic differentiation grade, T-stage, nodal metastasis, stage were obtained from pathologic records. Results: Survivin expression were observed in 30 cases (53.6%). The expression of survivin showed no statistically significant correlation with histologic differentiation grade, T-stage, nodal metastasis, stage. HSP90 expression were observed in 31 cases (55.4%). The expression of HSP90 showed a statistically significant correlation with histologic differentiation grade (P=0.035) and stage (P=0.017). There were a significant correlation between survivin expression and HSP90 expression (P=0.018). Conclusion: Survivin and HSP90 was expressed in colorectal cancer. The expression of HSP90 correlates with histologic differentiation grade, stage. The above results suggest that HSP90 could be a prognostic marker of poor outcome in colorectal carcinoma. (J Korean Surg Soc 2006;70: 113-119) KCI Citation Count: 1